Distribution features of leafminer moth on Bolle's poplar Populus pyramidalis Borkh in Kiev city - Drazhnikova, А. V.; Popova, E. M. (Problems of Environmental Biotechnology, 2014)
The paper shows the results of monitoring studies of leafminer moth distribution on poplar trees in Kiev in 2012-2013. Trophic preferences of leafminer moth are determined depending on the damage degree of poplar leaves. Trophic polyphenism of leafminer moths is experimentally confirmed. It was grounded the possible explaining the emergence of leafminer moth on poplar trees as transition of widely distributed in Kiev horse-chestnut leafminer moth Cameraria ohridella on a new host-plant – poplar tree as a result of invasive parasitic mycobiota distribution on the leaves of horse-chestnut trees, such as powdery mildew Erysiphe flexuosa.